2015
DOI: 10.1074/jbc.m115.657114
|View full text |Cite
|
Sign up to set email alerts
|

NEU1 Sialidase Regulates Membrane-tethered Mucin (MUC1) Ectodomain Adhesiveness for Pseudomonas aeruginosa and Decoy Receptor Release

Abstract: Background: Pseudomonas aeruginosa flagellin binds to the membrane-tethered mucin, MUC1. Results: Flagellin drives NEU1 to desialylate MUC1, thereby increasing its adhesiveness for Pseudomonas aeruginosa and its shedding. Conclusion: P. aeruginosa hijacks host NEU1 through its flagellin. Significance: P. aeruginosa mobilizes NEU1 to enhance its pathogenicity, but the host retaliates by releasing MUC1 as a hyperadhesive decoy receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(100 citation statements)
references
References 45 publications
7
93
0
Order By: Relevance
“…Mucins and the monosaccharides that comprise O-linked glycans are conserved among many organisms. It had been previously reported that P. aeruginosa binding to human lung epithelial cells is reduced in the absence of specific mucins, namely, MUC1 (6,14,17,61). In addition, we have also demonstrated that monosaccharides reversed the binding defects observed in muc1-silenced cells, indicating that mucins may aid bacterial pathogenesis.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Mucins and the monosaccharides that comprise O-linked glycans are conserved among many organisms. It had been previously reported that P. aeruginosa binding to human lung epithelial cells is reduced in the absence of specific mucins, namely, MUC1 (6,14,17,61). In addition, we have also demonstrated that monosaccharides reversed the binding defects observed in muc1-silenced cells, indicating that mucins may aid bacterial pathogenesis.…”
Section: Discussionsupporting
confidence: 73%
“…One of the low-affinity binding mechanisms used by microbes is mediated by hydrophobic interactions with lectins and glycosylated receptors, including oligosaccharides and monosaccharides present on mucins (4,(11)(12)(13). In addition to serving as a binding site, individual monosaccharides from mucins can be accessed as energy sources by bacteria with mucolytic activity (14). Finally, mucus components can influence the virulence characteristics of pathogenic bacteria, such as virulence factor expression, adhesion, motility, proliferation, and/or growth (3,7,8,(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…43 Given the normal clathrin-mediated endocytosis pathway utilized for recycling extracellular MUC1 (ref. 6) and that a major route of infection by IAV is via incorporation of the virion into the endosome after attachment to a Neu5Ac-containing receptor, we found it surprising that MUC1 did not facilitate IAV infection of host epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bound bacteria were released with 0.05% trypsin, EDTA, and bound cfu were quantified on Luria-Bertani agar plates as described (60,61). Significance was determined by Student's t test.…”
Section: Methodsmentioning
confidence: 99%
“…Cell Adhesion-A549 human airway adenocarcinoma cells (52) (CCL 185, American Type Culture Collection (ATCC), Manassas, VA) or Detroit 562 pharyngeal carcinoma cells (53) (ATCC CCL 138) were seeded in 24-well culture plates and cultured at 37°C in 5% CO 2 to 2.0 ϫ 10 5 cells/well in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum, 2.0 mM glutamine, 100 units/ml penicillin, and 100 g/ml streptomycin. The cells were washed twice with PBS, pH 7.2; fixed for 10 min at room temperature with 2.5% (v/v) glutaraldehyde in PBS, pH 7.2; and washed three times with PBS, pH 7.2 as described (60,61). A. nosocomialis M2 was cultured overnight in Luria-Bertani broth; washed twice with PBS, pH 7.2; resuspended in PBS, pH 7.2 containing 2.0 mg/ml glucose; and quantified spectrophotometrically at A 600 .…”
Section: Methodsmentioning
confidence: 99%